Foaming of recycled crosslinked polyethylenes via supercritical decrosslinking reaction - Kwon, Yong Jin; Park, Wan Yong; Hong, Soon Man; Koo, Chong Min (WILEY, 2012)
Foaming of decrosslinked crosslinked polyethylene (DCXLPE) was investigated to assess the feasibility of recycled crosslinked polyethylene for polyolefin foam applications. DCXLPE was recycled from irradiation-induced crosslinked polyethylene using the supercritical methanol process. As the concentration of crosslinking agents increased, the gel fraction and hardness of the DCXLPE foam sheets increased, while the expansion ratio and cell size decreased. The resulting foam products not only revealed a viable foam structure and properties comparable with those of conventional polyethylene foam from virgin low-density polyethylene resin but also are expected to open new applications for recycled crosslinked polyolefin via supercritical decrosslinking reaction. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: LINKING; IRRADIATION